THE USE OF DIGITAL COMICS TO ENHANCE STUDENTS' LITERACY SKILLS: A STRUCTURED NARRATIVE REVIEW AND PEDAGOGICAL SYNTHESIS - Daniel Zulhendra; Faisal Faisal; Carlo Antonio Garcia (SENSEI RESEARCH CENTER, 2026)
Students nowadays like to read comics on their handphone more than reading the textbook. Digital comics have pictures and text so it is easier to understand, and it can be used for teaching literacy. This article discusses the use of digital comics to enhance students' literacy skills. The method used is literature review from various journals and books about comics and multimodal literacy. The result shows that digital comics can help the students in vocabulary, reading comprehension, multimodal literacy, digital literacy, and also critical literacy. However the comic must be selected carefully because sometimes the language is too difficult or the content is not suitable, and not all schools have the device. So the teacher must choose the comic and design the activity, not only ask the students to read.